First‐in‐Human Pharmacokinetics and Safety Study of GSK3008356, a Selective DGAT1 Inhibitor, in Healthy Volunteers - Okour, Malek; Gress, Angela; Zhu, Xinyi; Rieman, David; Lickliter, Jason D.; Brigandi, Richard A. (Clinical pharmacology in drug development, 2019)
Diacylglycerol acyltransferase (DGAT) enzymes are involved in triglyceride (TG) biosynthesis. GSK3008356 is a potent and selective DGAT1 inhibitor that was administered orally in a 2‐part study as double‐blind, randomized, placebo‐controlled single doses (SDs) and repeat doses (RDs) in healthy subjects to investigate its pharmacokinetics, pharmacodynamics, and safety/tolerability. Gastrointestinal adverse events were considered drug related and increased with dose and when given as multiple doses. In the SD part (n = 80), GSK3008356 was dosed from 5 to 200 mg as single or multiple doses per day. In the RD part (n = 24), GSK3008356 was dosed twice daily at 1, 3, and 10 mg for 14 days. GSK3008356 was generally well tolerated in the SD and RD parts. With single doses, absorption was rapid (median tmax, 0.5–1.5 hours), whereas single‐day divided dosing resulted in higher tmax. Following 14‐day RD oral administration, GSK3008356 was also rapidly absorbed, with median tmax ranging from 0.5 to 0.75 hours on days 1 and 14. Estimated mean half‐life ranged from 1.5 to 4.6 hours with SDs and 1.3 to 2.1 hours with RDs. Exposure of GSK3008356 was largely dose proportional after RDs. At higher doses, there was a trend toward lower absolute postprandial TG level in some subjects.